Long-Term Abnormal Returns of Takeovers: The Impact of Merger and Acquisition on China Company Performance - Zhou, Ling (2008)
This paper tends to examine the long-run postacquisition abnormal returns of bidding firms in the Chinese market. We apply the buy-and-hold abnormal return (BHAR) and risk-adjusted factor model to estimate the abnormal returns. By testing 30 acquisitions that selected from the Chinese stock markets during 1997 to 2007, we find the bidding-firm shareholders earn normal returns in the long-run period. We also find a relationship between the postacquisition returns and the form of payment. The evidence indicates that firms merged with cash earn significant positive abnormal returns while stock merger earn significant negative abnormal returns. Our results also indicate a difference between the stocks with high book-to-market ratio (value stocks) and the stocks with low book-to-market ratio (glamour stocks). Generally speaking, value stocks are outperformed while glamour stocks do not. But both value acquirers and glamour acquirers do not earn statistically abnormal returns.